KAJIAN PENGENDALIAN PROSES PADA UMKM TAHU PAK SUWARYO KELURAHAN CILACAP, CILACAP SELATAN - Aldias Rezki Reyvaldi; Alfatha Rizal Febrianto; Bernika Irnadiani Ifadah; Figo Ardita Panggih Dwitama; Sari Widya Utami (PPPM POLTESA, 2025)
Tofu is one of the staple foods of Indonesian people which is rich in protein and as an alternative source of protein to replace fish and eggs. UMKM Tahu Pak Suwaryo located in South Cilacap has been producing tofu traditionally since the 1980s to meet the needs of the local market. The purpose of this study was to analyze the tofu production process and identify non-compliance with the principles of Good Manufacturing Practices (GMP) applied in the UMKM. The method used was descriptive qualitative through interviews and direct observation at the location. The results of the study showed that there were still various shortcomings in aspects of cleanliness, sanitation, use of Personal Protective Equipment (PPE), and the absence of Standard Operating Procedures (SOP) in several stages of production. In addition, the use of traditional equipment and minimal maintenance of equipment also have the potential to reduce product quality and safety. Therefore, the implementation of good process control, increasing cleanliness standards, and improving tools and work procedures are very important in order to increase the efficiency, effectiveness, and competitiveness of local tofu products in a sustainable manner. The purpose is to find out the implementation of GMP in UMKM Tahu Pak Suwaryo.